Grab It Fast! Entrepreneurial Self and Hyper-Consumerism in the Students’ Prosumption of Online Lending Services in Indonesia - Ratna Noviani; Heru Nugroho; Elok Santi Jesica (SAGE Open, 2025)
This study examines how students engage in the prosumption (production-consumption) of online lending services in Indonesia and how these services contribute to students falling into the trap of hyper-consumerism. Using multi-sited ethnography, this study explores how Cicil’s online lending practices, an online lending platform targeting higher education students in Indonesia, have challenged the prevailing stereotypes of lending practices in Indonesia. Within the prosumerism and sharing economy framework, Cicil constantly persuades students to participate in digital works, presenting them as valuable opportunities to be future entrepreneurial selves. At the same time, Cicil constantly allures students to partake in hyper-consumerism and steers them toward a cycle of loan-driven consumption. Through its services, the online lending platform employs an integrative strategy and participatory management to obscure the practice of domination.